Validation of a Procedure for Potency Assessing of a High Purity Factor VIII Concentrate -Comparison of Different Factor VIII Coagulant Assays and Effect of Prediluent - Mazurier, Claudine; Parquet-Gernez, Armelle; Goudemand, Maurice (Thrombosis and Haemostasis, 1990)
The assessment of factor VIII coagulant activity (FVTII: C) in recently available highly purified and concentrated FVTII therapeutic products calls for careful evaluation of assay methodologies. We assayed more than 130 batches of a concentrate with a specific activity of about 150 FVTII :C units/mg protein, using one-stage and two-stage clotting and chromogenic methods. There was good agreement between the potency estimates obtained with the different methods. We also compared the FVTII :C potencies obtained after predilution in buffer or FVIII-deficient plasma using either calibrated plasma or FVTII concentrate as references. With the one-stage assay we found a marked discrepancy between the potency values obtained with buffer and with FVTII-deficient plasma used as prediluents. In order to validate our “in vitro” data we performed 6 “in vivo” analyses in severe haemophilia A patients. On the basis of the overall data obtained we chose to label FVIII potency by using FVIII-deficient plasma as prediluent, reference plasma as standard and the chromogenic assay method.